The Artemis workbench for system-level performance evaluation of embedded systems. (15th September 2008) - Pimentel, Andy D.
In this paper, we present an overview of the Artemis workbench, which provides modelling and simulation methods and tools for efficient performance evaluation and exploration of heterogeneous embedded multimedia systems. More specifically, we describe the Artemis system-level modelling methodology, including its support for gradual refinement of architecture performance models as well as for calibration of the system-level models. We show that this methodology allows for architectural exploration at different levels of abstraction while maintaining high-level and architecture independent application specifications. Moreover, we illustrate these modelling aspects using a case study with a Motion-JPEG application.